Phylogenetic, clinical, pathological and epidemiological characterization of feline coronavirus infections in cats, in Istanbul - Yuzbasioglu Ozturk, Gulay; Kayar, Abdullah; Erdogan Bamac, Ozge; Tali, Hasan Emre; Ozkan, Ismail Egemen; Umar, Sajid; Aydin, Ozge; Cizmecigil, Utku Yusuf; Iskefli, Onur; Bayrakal, Alper; Turuncoglu, Fikriye Suzer; Kaan Tekelioglu, Bilge; et al. (Frontiers in Veterinary Science, 2025)
IntroductionFeline coronavirus (FCoV) is a widespread viral infection affecting domestic and wild cats globally, with higher prevalence in young cats and multi-cat environments.MethodsIn this study, a total of 208 clinical samples (blood, fecal, ascitic fluid, pleural fluid, tissue) were collected between January 2018 and January 2020 from diseased cats. Clinical and demographic data were recorded, and hematobiochemical and molecular detection analyses were performed.ResultsA total of 189 blood samples (90.9%) were found seropositive for FCoV, while 79 fecal samples (38%) were found positive for FCoV RNA by real-time RT-qPCR. No significant association was found between FCoV-RNA positivity and age or gender, while a significant association was found with crossbreed cats (p < 0.05). Notable clinical signs included weight loss (47%), dullness (44%), respiratory distress (16%), vomiting (13%), ascites (13%), epileptic fits (13%), diarrhea (6%), and fever (5%). Fever, depression, diarrhea, and ascites were significantly more common in PCR-positive cats than in PCR-negative cats (p < 0.05). The relationship between FCoV-RNA positivity and hematobiochemical indices was variable. Elevated monocyte and neutrophil levels were observed in 51 and 29% of cases, respectively. Additionally, elevated ALT activity and bilirubinemia were detected in 19 and 28% of cats, respectively. Partial S gene nucleotide analysis showed a deletion of multiple nucleotides in all sequences obtained in the present study. Interestingly, these deletions were absent in all reference strains belonging to FCoV type 2. Among 68 FCoV strains, 42 formed a separate cluster with the reference strain (AY307020) during phylogenetic analysis. This cluster was further divided into several small sub-clusters. Several unique recombinant events and recombination signals were observed among partial S1 gene sequences. Notable histopathological findings included fibrinous serositis and pyogranulomatous inflammation in vital organs.DiscussionThis study provides comprehensive information on FCoV infections among cats in Turkey. The findings could significantly contribute to understanding the hematobiochemical manifestations, epidemiology, and risk factors associated with FCoV, ultimately aiding in the development of better prevention and treatment strategies. A continuous molecular surveillance program is required to understand the evolution and emergence of virulent strains of FCoV to design new antiviral therapies and vaccines.